A NEW SPECIES OF BULBOPHYLLUM (ORCHIDACEAE) FROM NEPAL - Raskoti, B. B.; Ale, R. (Edinburgh Journal of Botany, 2013)
Bulbophyllum nepalense Raskoti & Ale (Orchidaceae) from Nepal is described and illustrated. Notes on the diagnostic characters used to distinguish it from the similar species Bulbophyllum retusiusculum are provided.
Keywords: Nepal; new taxa; orchids